Atypical presentation of hand-foot-mouth disease. Case report. - Chiriac, A.; Pinteala, T.; Chiriac, A.E.; Manea, P. (European Journal of Pediatric Dermatology, 2012)
A 4-year old boy came for examination from the Pediatric Department due to a widespread papular and vesicular eruption, fever (38.6 C°degrees), malaise, vomiting, abdomminal discomfort and diarrhea with sudden onset 24 hours before admitting to the hospital. These symptoms were preceded by mild irritability and small erosions on the tongue. On dermatological examination, there was an asymptomatic widespread eruption, consisting of papules and vesicles on an erythematous base and a few crusts, distributed on the palms, feet, face, earlobes, perianal region, gluteal area, lower limbs. At the time of examination the child was in good condition, with no fever, no digestive symptoms. The laboratory examinations showed only mild anemia. Serological tests for hepatitis (A, B, C) virus, Epstein-Barr virus, Cytomegalovirus, Mycoplasma, Chlamydia and Coxiella were negative. IgG antibodies for varicella-zoster virus were elevated. Virological test for Enterovirus 71 was positive in the stool (DIAQUICK Adenovirus Cassette, DIALAB, Italy). The clinical and laboratory findings, in an epidemic context, led to diagnose hand-foot-mouth disease.